Komparasi Profitabilitas Petani Anggota P3A Subur Estu, Desa Rembes, Kecamatan Bringin Terhadap Bantuan P3-TGAI - Paramitha, Saffana Zahra; Santoso, Siswanto Imam; Budiraharjo, Kustopo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyse the comparative profitability before and after receiving assistance from the Acceleration of Water Use Improvement Irrigation (P3-TGAI) Program for farmers who are members of P3A Subur Estu in Rembes Village, Bringin District. The research was conducted from November to December 2024. The research method used was survey with census sampling of 52 P3A members. The data used in this study are primary data and secondary data. Primary data were obtained from interviews, observations, and documentation. Secondary data were obtained from P3A member data and related literature studies. The analysis method used is quantitative descriptive analysis which aims to determine the condition of the business based on financial aspects. Quantitative descriptive analysis includes analysis of production costs, revenue analysis, income, and profitability before and after getting P3-TGAI assistance. The profitability results were compared using paired t test analysis. The results showed that the characteristics of respondents totalling 52 farmers, the majority were between 51-60 years old (35%), male (79%), and had a high school education level (50%). Most respondents had farming experience for 21-30 years (37%) with an average land area of 4,500 m2. The results showed that before receiving assistance, the average total production cost was Rp. 19,135,439, revenue of Rp. 50,723,077, average income of Rp 31,587,638, and average profitability of 165%. After receiving assistance, the average total cost was Rp. 19,567,113, revenue was Rp. 72,475,000, average income was Rp. 52,907,887, and average profitability was 270%. It is known that the average profitability of farming increased from 165% to 270% after receiving P3-TGAI assistance or an increase of 105%. The analysis results showed that there was a significant difference before and after receiving P3-TGAI assistance.